A STATISTICAL STUDY ON KEY PERFORMANCE INDICATORS IN HEALTH SYSTEM - Lucian MIRESCU; Ana-Maria Camelia POPESCU (Management & Marketing)
In this paper, a statistical study on key performance indicators in health system is given and two regression models with the average cost of hospitalization as the dependent variable are found. Using linear regression, it was found that a decrease in the average cost per day of hospitalization can be achieved by increasing the bed utilization rate and increasing the number of cases treated in a calendar year. Also, the decrease in the case-mix index, which can be achieved by increasing the number of resolved cases, leads to a decrease in the average cost of hospitalization per day. The obtained results were interpreted and certain measures are proposed to improve health management.